2015
DOI: 10.1097/igc.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Heparanases 1 and 2 in Benign Tissue and in Invasive Neoplasia of the Endometrium: A Case-Control Study

Abstract: Heparanase 1 is more intensely expressed in the glandular tissue of high-grade compared with type I carcinomas. Heparanase 2 is more intensely expressed in the glandular tissue of cancer than in nonneoplastic endometrium, whereas the HPSE2 expression in the stromal tissue is higher in the nonneoplastic controls compared with the group of patients with cancer mainly in the secretory endometrium. This suggests that HPSE2 might be stimulated by progesterone, with a possible antineoplastic role, antagonist to HPSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Some authors have described an increased expression of HPSE2 in tumor tissues [10], [11]. HPSE2 can also modulate the catalytic activity of HPSE [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have described an increased expression of HPSE2 in tumor tissues [10], [11]. HPSE2 can also modulate the catalytic activity of HPSE [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, the finding of increased HPSE2 expression in tumoral tissues in patients with lymph node metastases from CRC, compared to the HPSE2 expression in tumor tissue obtained from patients without lymph node metastases suggests that this protein may be related to molecular mechanisms of invasion and migration of tumor cells. Data from the literature have already proven a differential expression of HPSE2 in the cervix, endometrium, and thyroid cancer [38][39][40]. The fact that increased HPSE2 expression is directly related to tumors of patients with lymph node metastases possibly indicates that the HPSE2 expression might be useful to evaluate lymph node metastasis events.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted January 5, 2021. ; https://doi.org/10.1101/2021.01.05.425386 doi: bioRxiv preprint and thyroid cancer [38][39][40]. The fact that increased HPSE2 expression is directly related to tumors of patients with lymph node metastases possibly indicates that the HPSE2 expression might be useful to evaluate lymph node metastasis events.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the L1CAM [386], HSD17B2 [387], GRP (gastrin releasing peptide) [388], FABP4 [389], SOX6 [390]. MMP12 [391], APOD (apolipoprotein D) [392], LAG3 [393], CST1 [394], FLT1 [395], DHCR24 [396], PRL (prolactin) [397], WNT5A [398], TIMP3 [399], CD24 [400], LHCGR (luteinizing hormone/choriogonadotropin receptor) [401], MMRN1 [402], CD4 [403], ADAMTS5 [404], ADAMTS1 [405], PADI2 [406], MARK1 [407], KL (klotho) [408], PLAU (plasminogen activator, urokinase) [409], SOX8 [410], CRABP2 [411], PTPRD (protein tyrosine phosphatase receptor type D) [412], EPCAM (epithelial cell adhesion molecule) [413], IRX2 [414], SEMA3B [415], CYP1A1 [416], PDGFD (platelet derived growth factor D) [417], LEPR (leptin receptor) [418], APOE (apolipoprotein E) [419], CASP1 [420], MGLL (monoglyceride lipase) [421], NID1 [422], ABCG2 [423], ACE (angiotensin I converting enzyme) [424], PGR (progesterone receptor) [425], HPSE2 [426], LMTK3 [427], ALPP (alkaline phosphatase, placental) [428], EGFL6 [429], CACNA2D3 [430], MCTP1 [431], HKDC1 [432], S100A4 [433], MACC1 [434], MMP3 [435], FGFR2 [436], IL33 [437], FOXC2 [438], ITGA7 [439], EFEMP1 [440], GATA6 [441], BHLHE41 [442], TCF21 [443], GDF10 [444], NKX3-1 [445], AKR1C3 [446], SGK1 [447], RAP1GAP [448], FLI1 [449], NOX4 [450], SERPINE2 [451], IGSF9 [452], IGF2BP1 [453], SALL4 [454], VDR (vitamin D receptor) [455], CELSR2 [456],...…”
Section: Discussionmentioning
confidence: 99%